Assessment of the engineering properties, carbon dioxide emission and economic of biomass recycled aggregate concrete: A novel approach for building green concretes. (10th September 2022) - Ni, Songyuan; Liu, Haibao; Li, Qiuyi; Quan, Hongzhu; Gheibi, Mohammad; Fathollahi-Fard, Amir M.; Tian, Guangdong
Abstract : This paper presents an experimental study on the effects of using agricultural waste coconut shells for producing synthesized biomass recycled aggregate (SBRA) and replacing natural aggregate (NA) with its equivalent amount on the durability, thermal conductivity, carbon dioxide emissions, and economics of concrete. Test results show that the 3-day and 28-day compressive strength of concrete with the addition of SBRA - Class III reached 93% and 88% of natural aggregate concrete (NAC), respectively. In addition, using SBRA can effectively reduce the thermal conductivity of concrete, which shows great potential for building energy conservation. Compared with NA, the use of SBRA can reduce CO2 emissions and the cost of concrete by 2% and 5.9–7%, respectively. And the compressive strength - CO2 emission efficiency and compressive strength - cost efficiency are comparable to NA.